Answer:
pls mark brainy
Step-by-step explanation:
option (d) is correct.
An equivalent form of the given compound inequality −44 > −2x − 8 ≥ −8 is −44 > −2x − 8 and −2x − 8 ≥ −8
Step-by-step explanation:
Given a compound inequality −44 > −2x − 8 ≥ −8
We have to write an equivalent form of compound inequality.
Compound inequality consists of two inequalities joined together and the solution is the intersection of each inequality.
Compound inequality has two sides the left hand side and right hand side we can solve them by taking each inequality one at a time.
For given compound inequality, −44 > −2x − 8 ≥ −8
we have
Left side of inequality as −44 > −2x − 8
and right side of inequality as −2x − 8 ≥ −8
Thus, option (d) is correct.
Thus, An equivalent form of the given compound inequality −44 > −2x − 8 ≥ −8 is −44 > −2x − 8 and −2x − 8 ≥ −8
Step-by-step explanation:
"In three years, Tonya will be 17."
14 + 3 = 17, so Tonya is 14 atm. (At The Moment)
"Tonya is twice Kevin's age." Kevin is 7, because 7 x 2 = 14.
"In another three years, Uncle Rob will be three times Tonya's age."
Since Tonya is 14, multiply 14 x 3 and you get 42.
If you're asking for the three years, 17 x 3 = 51 < Uncle Rob's age
Kevin is about 8 1/2 years old. Since 8 x 2 = 16, I multiplied 8 1/2 x 2 and got 17.
I hope this helped.
Answer:
x
8
−
256
Rewrite
x
8
as
(
x
4
)
2
.
(
x
4
)
2
−
256
Rewrite
256
as
16
2
.
(
x
4
)
2
−
16
2
Since both terms are perfect squares, factor using the difference of squares formula,
a
2
−
b
2
=
(
a
+
b
)
(
a
−
b
)
where
a
=
x
4
and
b
=
16
.
(
x
4
+
16
)
(
x
4
−
16
)
Simplify.
Tap for more steps...
(
x
4
+
16
)
(
x
2
+
4
)
(
x
+
2
)
(
x
−
2
)
Step-by-step explanation:
It terminates <span>9÷16=<span>.5625</span></span>